2019
DOI: 10.3389/fmicb.2019.01595
|View full text |Cite
|
Sign up to set email alerts
|

Cecropin A Alleviates Inflammation Through Modulating the Gut Microbiota of C57BL/6 Mice With DSS-Induced IBD

Abstract: The present study is undertaken to assess the alleviating effects of antimicrobial peptide cecropin A on inflammatory bowel disease (IBD) in C57BL/6 mice and changes in the gut microbiota, compared to an antibiotic gentamicin. Different doses of cecropin A were intraperitoneally injected into C57BL/6 mice for 5 days to determine the safe doses. The injection doses at ≤ 15 mg/kg showed no negative impact on the liver, heart, spleen, and kidney. The severe and moderate IBD mice model was successfully established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 46 publications
4
68
0
Order By: Relevance
“…These data are counterintuitive in the light of our data presented here and given that this family may be an indicator of colitis disease activity. In contrast, in the study by Zhai Z. et al (2019) , Marinifilaceae positively correlated with inflammatory status in the mice, which is in line with our study describing significant decreases in this family at d8 by CBD (1 mg/kg) + FO (20 mg/mouse), concomitant to decreased inflammation. Furthermore, both Marinifilaceae and Ruminococcaceae were decreased in rats fed an acorn-fed cured ham diet (having high levels of the mono-unsaturated fatty acid oleic acid), in conjunction with significant prevention of DSS-induced colitis symptoms ( Fernandez et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data are counterintuitive in the light of our data presented here and given that this family may be an indicator of colitis disease activity. In contrast, in the study by Zhai Z. et al (2019) , Marinifilaceae positively correlated with inflammatory status in the mice, which is in line with our study describing significant decreases in this family at d8 by CBD (1 mg/kg) + FO (20 mg/mouse), concomitant to decreased inflammation. Furthermore, both Marinifilaceae and Ruminococcaceae were decreased in rats fed an acorn-fed cured ham diet (having high levels of the mono-unsaturated fatty acid oleic acid), in conjunction with significant prevention of DSS-induced colitis symptoms ( Fernandez et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, DSS-induced increases of Desulfovibrionaceae in mice were abrogated through treatment with the probiotic Bifidobacterium breve ( Yang and Yang, 2018 ). However, Desulfovibrionaceae and Ruminococcaceae were both increased by gentamicin in DSS-treated mice in association with an improved DAI and inflammatory profile ( Zhai Z. et al, 2019 ). Most interestingly, Ptpn22 −/− mice, which are resistant to faster recovery in response to cohousing-mediated faecal microbiota transfer, have decreased Desulfovibrionaceae levels ( Spalinger et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A very recent report from Zhai et al. 32 suggested that cecropin A alleviates inflammation by modulating the gut microbiota in mice with inflammatory bowel disease. Haney et al.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal colitis was induced in all mice by administration of 3% DSS (MP Biomedicals Shanghai, Co., Ltd. molecular weight=165.192 g/mol) in drinking water for seven days as previously described 26 . After that, thirty mice with colitis were obtained and randomly assigned into three groups (n =8) including the control group (Control) without EA (EA, Sigma-Aldrich,CAS141-43-5) supplements and two treatment groups that were supplemented with 500μM EA (LowEA) and 3000 μM EA(HighEA) in drinking water for two weeks( Figure 1A).…”
Section: Animals and Experimental Designmentioning
confidence: 99%